THE POMERON IN A MODIFIED MU LTIPERIPHERAL MODEL (Journal of Sciences, Islamic Republic of Iran)
There have been many attempts [I-31 to produce correct pomeron by putting the nparticle production amplitude expht, in the unitarity integral equation. It was found that for reasonable values of h one could not get the right picture of the slope of the pomeron as a function of energy S4 .W e show that theinterference termsin the unitary equation does not improve the slope either. However, a modified multiperipheral model predicts a correct pomerpn